Combines of the Leningrad Branch of the USSR Art Fund at the Beginning of the Thaw: Main Activities - Ananiev, Vitaly G. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2024)
This article examines the activities of the combines of the Leningrad branch of the USSR Art Fund in the mid- to late-1950s. During this period, the Leningrad branch of the USSR Art Fund comprised two combines with responsibilities related to the art industry: the Painting and Sculpture Combine and the Art and Design Combine. The materials preserved in the Central State Archive of Literature and Art of St Petersburg facilitate an understanding of the primary avenues through which the Art Fund influenced the formation of the living environment of Soviet citizens during the period under review. The shift from the period of late Stalinism to the Thaw era was accompanied by substantial alterations in the visual representation and structural configuration of this environment. The analysis of the activities of the combines permits a more precise understanding of the way these images were embodied, implemented, and disseminated at the level of specific production practices. The difficulties faced by the combines were a significant factor in adjusting the ideological framework in which their activities were to be based. The most important problem was the problem of unsatisfactory material and technical base, lack of modern equipment and trained personnel. Despite the government’s stated commitment to the role of decorative, applied, and industrial arts in shaping the living environment of Soviet citizens, the implementation of this policy was hindered by a lack of adequate funding. In many ways, the range of products was formed spontaneously. The artists themselves played a significant role in shaping it. Changes in the subjects and images of the products produced by the combines during the period of the early Thaw make it possible to trace exactly how the formation of the so-called Leningrad style took place. A significant factor here was the postponed celebration of the 250th anniversary of Leningrad, which also became one of the markers of the onset of a new political era. It seems that all the above-mentioned circumstances associated with the actual practices of producing elements of the living environment of a Soviet person should be considered when analysing the general plan of chamber propaganda of the era.